Risky Sexual Behavior Profiles in Youth: Associations With Borderline Personality Features - Bégin, Michaël; Ensink, Karin; Bellavance, Katherine; Clarkin, John F.; Normandin, Lina (Frontiers in Psychology, 2022)
Adolescence and young adulthood are peak periods for risky sexual behaviours (RSB) and borderline personality disorder (BPD) features. Adolescents with BPD may be particularly vulnerable to RSB, but this is understudied. The aim of this study was to identify distinct RSB profiles in youth and examine whether a particular profile was associated with BPD features. Participants were 220 adolescents and young adults (age 14–21) from a community sample. To identify groups of adolescents and young adults who engage in similar RSB, a latent profile analysis (LPA) was conducted on sexually active youth (57%). Next ANOVA was used to identify how profiles differed in terms RSB dimensions and BPD features. We identified three distinct RSB profiles with little to no overlap: 1) a Low RSB profile manifested by the majority (77.7%) of youth; 2) an Unprotected Sex in Relationships profile (13.3%) and; 3) an Impulsive Sex Outside Relationships profile (12%) which was associated with higher BPD features. The findings shed light on the difficulties youth with BPD manifest around integrating sexuality, intimacy, fidelity and love, and clearly show that the majority of sexuality active youth do not engage in RSB or do so in the context of relationships.